Pinworm diversity in free-ranging howler monkeys (Alouatta spp.) in Mexico: Morphological and molecular evidence for two new Trypanoxyuris species (Nematoda: Oxyuridae). Issue 5 (October 2016) - Solórzano-García, Brenda; Nadler, Steven A.; Pérez-Ponce de León, Gerardo
Abstract: Two new species of Trypanoxyuris are described from the intestine of free-ranging howler monkeys in Mexico, Trypanoxyuris multilabiatus n. sp. from the mantled howler Alouatta palliata, and Trypanoxyuris pigrae n. sp. from the black howler Alouatta pigra. An integrative taxonomic approach is followed, where conspicuous morphological traits and phylogenetic trees based on DNA sequences are used to test the validity of the two new species. The mitochondrial cytochrome oxidase subunit 1 gene, and the nuclear ribosomal 18S and 28S rRNA genes were used for evolutionary analyses, with the concatenated dataset of all three genes used for maximum likelihood and Bayesian phylogenetic analyses. The two new species of pinworms from howler monkeys were morphologically distinct and formed reciprocally monophyletic lineages in molecular phylogenetic trees. The three species from howler monkeys, T. multilabiatus n. sp., T. pigrae n. sp., and Trypanoxyuris minutus, formed a monophyletic group with high bootstrap and posterior probability support values. Phylogenetic patterns inferred from sequence data support the hypothesis of a close evolutionary association between these primate hosts and their pinworm parasites. The results suggest that the diversity of pinworm parasites from Neotropical primates might be underestimated. Graphical abstract: Highlights: Two new species of Trypanoxyuris are described from howler monkeys in Mexico. Buccal structure, lateral alae, and oesophagus are main diagnostic traits. Trypanoxyuris from howler monkeys form a monophyletic clade in molecular phylogenetic analyses. Parasite-host associations provide insights into the possible origin of these pinworms. Evidence suggests that pinworm diversity in Neotropical primates has been underestimated.